Developing high temperature tolerance in tomato (Solanum lycopersicum L.) through selective fertilization technique - Ammu Alphonsa John (Department of Plant Physiology, College of Agriculture, 2019)
The study entitled “Developing high temperature tolerance in tomato (Solanum lycopersicum L) through selective fertilization technique”, was undertaken with the objectives to identify the critical temperature for pollen germination and to evaluate the selectively fertilized tomato hybrids for high temperature tolerance at the Department of Plant Physiology, College of Agriculture, Vellayani during 2017-2019. The first experiment was designed for the identification of critical temperature for pollen germination using five popular varieties of tomato namely Anagha, Vellayani Vijay, Manuprabha, Manulakshmi and Akshaya. Mature pollen grains from fully opened flowers were collected and incubated at different temperatures (340C to 440C) for two hours in the pollen germination medium. The design followed was CRD with 4 replications. The temperature of 36oC was identified as the critical temperature for pollen germination. Anagha and Manuprabha exhibited the highest (29.69 %) and the least (11.48 %) pollen germination percentage respectively at this critical temperature. Pollen viability decreased with increase in temperature in all the five varieties. For the second experiment, the variety Anagha with the highest pollen germination at critical temperature was selected as tolerant (male parent) and the variety Manuprabha with least pollen germination at critical temperature was selected as the susceptible (female parent). Selective fertilization (SF) was done between Anagha and Manuprabha by pollinating the emasculated female parent with 2hr incubated pollen from male parent at critical temperature. Another set of cross was also made with same parental combination without pollen selection. The six crosses were made are Tolerant X Susceptible, Tolerant X Susceptible (SF), Tolerant X Tolerant, Tolerant X Tolerant (SF), Susceptible X Susceptible and Susceptible X Susceptible (SF). The seeds were collected from crosses and sown. The seedings were maintained at ambient temperature for 30 days and then transplanted in pots and exposed to three different temperature conditions ie, at ambient temperature condition, Rainout shelter (ROS) and Open top chamber (OTC) to evaluate the growth performance of the crosses. The observations were taken at 30 and 60 days after transplanting. The experiment was laid out with 18 treatments in CRD with four replications. Plant height and floral characters (number of flower clusters and number of flowers per cluster) were increased significantly with increase in temperature. Among the crosses, T15 recorded taller plants (127.32 cm). Selectively fertilized plants produced significantly more number of flowers per cluster than the normal crosses and T12 recorded maximum (11.00). However, the number of cluster was significantly higher in normal crosses and T15 had maximum number of cluster (45.50). Percentage of flowers with exerted stigma and length of stigma exertion were increased significantly with increase in temperature but the selectively fertilized crosses recorded lower stigma exertion. T15 showed the highest percentage stigma exertion (87.50%) which was at par with T3, T6, T9, T12 and T18. The length of exerted stigma was highest in T15 (2.50mm). Physiological parameters like photosynthetic rate, chlorophyll content, total soluble protein and relative water content decreased significantly with increase in temperature and the selectively fertilized crosses showed higher value than the normal crosses under higher temperature. The photosynthetic rate (17.40 µmol CO2 m-2 s-1) and chlorophyll content (1.91 mg g-1) was recorded higher in T7 which was at par with T1, T4, T10 and T11. In case of total soluble protein there was no significant difference. The relative water content was highest in T4 (74.80%) but at par with T1, T7 and T10. Carbohydrate content decreased with increasing temperature and among the crosses selectively fertilized plants showed significantly higher content. The carbohydrate content was the highest in T8 (79.62 mg g-1) but at par with T5. Temperature tolerance characters like membrane integrity (% leakage), SOD activity and chlorophyll fluorescence were higher in selectively fertilized plants than the normal plants. The percentage leakage increased with increase in temperature and T10 had the least leakage (1.40 %). The SOD activity first decreased and then increased with temperature and T5 exhibited maximum SOD activity (337.50 activity mg-1 min-1) which was at par with T2 and T8. The chlorophyll fluorescence significantly decreased with increase in temperature, the maximum fluorescence recorded in T4 (0.65 fv/fm) which was at par with T1, T7, T10, T16 and T5. Ascorbic acid content of leaves increased significantly with increase in temperature but decreased under OTC. T5 (464.65 µg g-1) and T18 were on par with respect to ascorbic acid. The yield characters like number of fruits, fruit setting %, fruit weight and lycopene content were high in selectively fertilized crosses than the normal crosses. The yield characters decreased significantly with increase in temperature and there was no fruit set at OTC due to very high temperature. T10 recorded highest number of fruits per cluster (6) which was at par with T7 and T1. The fruit setting percentage was the highest in T7 (89.29%) which was at par with all treatments except T2 and T14. The fruit weight increased in ROS condition compared to ambient condition and the highest fruit weight was recorded in T17 (37.77g) which was at par with T16, T5 and T14. Highest lycopene content was recorded in T10 (24.86 µg g-1). The yield was decreased significantly with increase in temperature and the highest yield was obtained in T4 (402.15 g plant-1) which was at par with T4, T7 and T10. Critical temperature for pollen selection and selective fertilization was selected as 360 C. Anagha exhibited higher germination percentage and pollen viability at critical temperature among the five varieties of tomato tested and Manuprabha had the least pollen germination. Selective fertilization technique was found to have an advantageous influence on the physiological and yield attributes as it increased the photosynthetic efficiency and high temperature stress tolerance. Selective fertilization of cross of tolerant and susceptible parent TXS (SF) was found to be the best performing type under high temperature condition.